(untitled) (Journal of the College of Basic Education, 2022)
Through the development of the concept of focus, we see that it has gone through advanced stages, and this development, which took place on many critical books and narrative studies, made it one of the most prominent and important terms used, as it reached the center stage in studies and research, and this gave it several names (vision, point of view, or perspective).